Perancangan Sistem Informasi Pencatatan Form Order Berbasis Web pada PT. United Trans Perkasa - Yulianus Palopak; Romario S.L Tobing (TeIKa, 2020)
The evolution of information technology greatly affects various types of jobs in this world. Business competition encourages companies to use technology for support business processes. One of the fundamental reasons for this research’s PT. United Trans Perkasa doesn’t yet have a computerized system in the company’s business processes, especially in terms of managing data orders. The purpose of this study are: (1) Makes it easier for companies to find the order data that has been recorded, (2) Makes it easier for workers to know the arrival of orders from each customer, and (3) Makes it easier for workers to send data that needs to be reported to the leadership of the company. The design of this system uses the Waterfall Method, which approaches the design process systematically, which starts at the level of system analysis, design, code, and testing. The conclusions of this study are: (1) Information system for recording the order form at PT. United Trans Perkasa is a system created to simplify work and also improve services in serving customers, (2) Information system for recording order forms at PT. United Trans Perkasa can present important data in a computerized company and also based online, so that the data can be accessed by office workers anywhere and anytime. (3) Information system for recording the order form at PT. United Trans Perkasa can also facilitate the company in checking customers who want to use company services, because this system is connected to the company's website.